Tunneled Tunica Vaginalis Flap for Recurrent Urethrocutaneous Fistulae - Jonathan C. Routh; James J. Wolpert; Yuri Reinberg (Advances in Urology)
The tubularized incised plate (TIP) hypospadias repair is currently the most widely used urethroplasty technique. The most significant post-TIP complication is urethrocutaneous fistula (UCF) development. Tunneled tunica vaginalis flap (TVF) is a well-described technique for the repair of UCF. We retrospectively reviewed all patients undergoing repeat repair of UCF after TIP repair from 2001 to 2005. Twelve boys underwent TVF repair at our institution for recurrent UCF. Fistulae ranged from distal penile to penoscrotal in location. Median surgical time was 45 minutes and no postoperative complications occurred. After a median follow-up of 32 months (range 16–48 months), no patient has yet had a recurrence of UCF. In conclusion, TVF repair is a successful technique for the treatment of UCF after previous failed repair. TVF is technically simple to perform and should be considered for treating UCF following TIP urethroplasty, particularly in a repeat surgical setting.